Influence of silicate anions structure on desilication in silicate-bearing sodium aluminate solution - Liu, Gui-hua; Zhang, Wen; Qi, Tian-gui; Peng, Zhi-hong; Zhou, Qiu-sheng; Li, Xiao-bin (Journal of Central South University, 2016)
The structural changes of silicate anions in the desilication process with the addition of calcium hydrate alumino-carbonate were studied by measuring Raman spectra, infrared spectra and corresponding second derivative spectra. The results show that the desilication ratio in the solution prepared by the addition of sodium silicate (solution-SS) is much greater than that in the solution by the addition of green liquor (solution-GL), and low alumina concentration in the sodium aluminate solutions facilitates the desilication process. It is also shown that alumino-silicate anions in the solution-GL, and Q 3 polymeric silicate anions in solution-SS are predominant, respectively. In addition, increasing the concentration of silica favors respectively the formation of the alumino-silicate or the Q 3 silicate anions in the solution-GL or the solution-SS. Therefore, it can be inferred that the low desilication ratio in the silicate-bearing aluminate solution is mainly attributed to the existence of alumino-silicate anions.